Cyber security crisis/threat: analysis of Malaysia National Security Council (NSC) involvement through the perceptions of government, private and people based on the 3P Model - Siti Sabrina Imji Rahim,; Mohd Ikbal Mohd Huda,; Shahrizal Sa’ad,; Ravichandran Moorthy, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The new crisis/threat namely cyber security has become a priority for Malaysia due to the huge impact not only on this country, but also the people. Malaysia shows a trend of increasing cyber security despite various initiatives taken by the government to deal with it. The government has established the National Cyber Security Agency (NACSA) under the auspices of the National Security Council (NSC) where NACSA acts to coordinate all forms of cyber management with other agencies that handle cyber in Malaysia. The question arises is why cyber security continues to increase which is necessary to analyze to what extent NSC as a coordinating agency for managing cyber security successfully plays its role. The study carried out by analyzing the perception of the government, the private sector, and the people on the effectiveness of NSC 's involvement based on the 3P Model via qualitative methods that refer to primary and secondary documents such as official reports, academic journals, and online news as well as through interviews with government officials involved. The results of the analysis found that NSC's involvement is proactive in dealing with cyber security. NSC's coordination with other agencies is active, but there are challenges that need to be addressed. Coordination between the central and state NSC is effective. Political interference has influenced the determined decision but minimal. Cyber security management has led NACSA/NSC to updating/drafting the laws, increased program/strategy, more prominent, and collaborative involvement of all parties.